2003
DOI: 10.1002/bjs.4045
|View full text |Cite
|
Sign up to set email alerts
|

Factors predictive of 5-year survival after transarterial chemoembolization for inoperable hepatocellular carcinoma

Abstract: Five-year survival is possible with TACE for inoperable HCC, even in some patients with advanced tumours. Unilobar tumours, alpha-fetoprotein level below 1000 ng/ml and albumin concentration greater than 35 g/l were factors predictive of 5-year survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
56
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(65 citation statements)
references
References 28 publications
8
56
1
Order By: Relevance
“…In the current study, the factors that were significant in multivariate analysis were similar to the factors that constitute the CLIP score, and they also were similar to the factors determined in previous studies of TACE. 28,29 The most powerful prognostic factor of poor survival was vascular invasion in this study, and similar results were reported in patients who underwent liver resection or transplantation. 1,[30][31][32] Although the BCLC system was validated as the most suitable prognostic system for patients with HCC in Italy and the United States, it was not considered a suitable prognostic system in the Eastern countries until now.…”
Section: Discussionsupporting
confidence: 88%
“…In the current study, the factors that were significant in multivariate analysis were similar to the factors that constitute the CLIP score, and they also were similar to the factors determined in previous studies of TACE. 28,29 The most powerful prognostic factor of poor survival was vascular invasion in this study, and similar results were reported in patients who underwent liver resection or transplantation. 1,[30][31][32] Although the BCLC system was validated as the most suitable prognostic system for patients with HCC in Italy and the United States, it was not considered a suitable prognostic system in the Eastern countries until now.…”
Section: Discussionsupporting
confidence: 88%
“…As expected these patients had lower survival rates. However, with minor differences depending on the group of patients selected and treatment modalities chosen, similar results were reported by others (Stuart et al, 1996;Allgaier et al, 1998;Bruix and Llovet, 2002;Herold et al, 2002;O'Suilleabhain et al, 2003).…”
Section: Discussionsupporting
confidence: 87%
“…In contrast to a series of other published studies (Chevret et al, 1999;Llovet et al, 1999; The Cancer of the Liver Italian Program, 2000; Villa et al, 2000;Rabe et al, 2001;Herold et al, 2002), this study included a high number of patients treated by TACE and PEI, which have become the most frequently used treatments in the Western World. No patient was excluded from our retrospective analysis in contrast to those studies, who investigated only the effect of surgery or local ablative therapy (Tanaka et al, 1998;Schlitt et al, 1999;O'Suilleabhain et al, 2003;Jaeck et al, 2004). Therefore, this data reflects the current situation, for unselected patients with HCC similar to a different study published 9 years ago (Stuart et al, 1996).…”
Section: Discussionmentioning
confidence: 76%
“…However, in the US, where there is no national screening program, the majority of HCC patients present at an advanced phase of their disease, either due to the severity of the underlying cirrhosis or the extent of their HCC. There has not so far, to our knowledge, been a large prospective study of these advanced unresectable HCC patients; although, several small series having evaluated prognostic factors in these patients [8,20,[24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%